Penitentiary pleasures: Queer understandings of prison paradoxes - Vasiliou, Elena (Criminology & criminal justice, 2020)
Historically, prison researchers have remained disengaged with explorations of pleasure in punishment because of the risk of romanticizing imprisonment. This risk is inherent in any discussion of pleasure experienced by prisoners. In this article, I advocate for the application of queer theory as a means of deconstructing the binary formation through which pain and pleasure in prison is understood. To do that, I explore how ex-prisoners’ narratives might reveal (queer) moments of pleasure and complement existing criminological scholarship that has neglected such an issue. This exploration is framed by Foucault’s theory of pleasure as a productive force that renders it akin to power: it produces an effect. In this article, I draw on Edelman’s concept of “futurity” and Halberstam’s “failure” to bring criminology and queer theory into a productive dialogue for the purpose of analyzing the production of narratives of pleasure by ex-prisoners. In my analysis, I use Jackson and Mazzei’s “plugging in method” centered around the categories of (a) pleasure and pain, (b) pleasure and resistance, and (c) sexuality and pleasure. Drawing upon the findings, I argue that pleasure becomes a nexus of relations that exists and correlates with sexuality, power/resistance, and the feeling of pain. I conclude that a queer understanding of what is unpleasant is possible if we reconsider pleasure and pain in a spectrum as opposed to a binary formation.